REVIEWS (Heythrop journal, 1971)
Book reviewed in this article Logical Investigations. By Edmund Husserl. Translated from the second German edition of Logische Untersuchungen by J. N. Findlay. Vols. 1, 2. Fallacies. By C. L. Hamblin. The Brain-Mind Identity Theory. Edited by C. V. Borst. Respect for Persons. By R. S. Downie and Elizabeth Telfer. The Sovereignty of Good. By Iris Murdoch. What is Redaction Criticism? By Norman Perrin. In Search of the Historical Jesus. Edited by Harvey K. McArthur. New Testament Issues. Edited by Richard Batey. The Resurrection of Jesus of Nazareth. By Willi Marxsen. Translated by Margaret Kohl. Catholic Theories of Biblical Inspiration since 1810. By James T. Burtchaell. Encyclopaedia of Biblical Theology. Edited by J. B. Bauer. Translated by J. Blenkins New Liturgical Feasts in Later Medieval England. By R. W. Pfaff. The Yale Edition of the Complete Works of St. Thomas More: Volume 5: Responsio ad Lutherum, Part I: Latin and English Texts; Part II: Introduction, Commentary, Index. Edited by John M. Headley. The New Cambridge Modern History. Volume VI. The Rise of Great Britain and Russia 1688–1725. Edited by J. S. Bromley. Philosopher King. The Humanist Pope, Benedict XIV. By Renée Haynes. Irish Anglicanism 1869–1969. Edited by Michael Hurley, S. J. Classical Islam, A History 600–1258. By G. E. VON Grunebaum. Translated from the German by Katherine Watson.